Gamifying Grammar Games (3G) for language learning: Engaging students in learning through GIGvaganza. (Get into Grammar) in ECER programme - Noor Azlinda, Zainal Abidin (Universiti Malaysia Pahang, 2019)
Gamifying in language learning is not something new in English language teaching. Teachers have put much efforts in ensuring fun learning is created to motivate students in learning. Learning thus does not end in the classroom but it has to be done outside class hours as well. In engaging the students in language learning, GIGvaganza was introduced as one of the modules for Empower Programme which was funded by East Coast Economic Region (ECER). The study was carried out to find out the impact of this programme towards the students in Kuantan district who are involved in this programme. Interviews were conducted to students and teachers in schools after the completion of the programme and it was analyzed by using thematic analysis. Results have shown that GIGvaganza has a positive impact on students’ learning. GIGvaganza does not only assist learning in Grammar but holistically, it changes their view on learning as learning itself becomes more meaningful with GIGvaganza.